UNIT 22.4 Multielectrode Array (MEA) Assay for Profiling Electrophysiological Drug Effects in Human Stem Cell‐Derived Cardiomyocytes. Issue 1 (4th May 2016) - Clements, Mike
Abstract : More relevant and reliable preclinical cardiotoxicity tests are required to improve drug safety and reduce the cost of drug development. Human stem cell‐derived cardiomyocytes (hSC‐CMs) provide a potential model for the development of superior assays for preclinical drug safety screening. One such hSC‐CM assay that has shown significant potential for enabling more predictive drug cardiac risk assessment is the MEA assay. The Multi‐electrode Array (MEA) assay is an electrophysiology‐based technique that uses microelectrodes embedded in the culture surface of each well to measure fluctuations in extracellular field potential (FP) generated from spontaneously beating hSC‐CMs. Perturbations to the recorded FP waveform can be used as an unbiased method of predicting the identity of ion channel(s) impacted on drug exposure. Here, a higher throughput MEA assay using hSC‐CMs in 48‐well MEA plates is described for profiling compound‐induced effects on cardiomyocyte electrophysiology. Techniques for preparing hSC‐CM monolayers in MEA plates and methods to contextualize MEA assay experimental results are also covered. © 2016 by John Wiley & Sons, Inc.